Methodological Problems in Foreign Language Teaching: Is ict a Solution? - Zayas Martínez, Francisco (Rastros Rostros, 2014)
Foreign language teaching continues to be one of the issues to tackle in education. In recent decades, methodological approaches have prioritized communication over information around the way languages function, but this has not led to a marked improvement in results. The newest models only offer partial or seeming improvements to some elements of teaching and learning processes. Editors’ systematic misunderstanding of the process as a whole has turned methodological proposals into teaching fads that are superficial, unproductive, and quick to fade away. In recent years we have looked to ict to provide a way forward. This article argues that the quantity and immediacy of digital resources and telematics do not in themselves improve the efficacy of language teaching; they will only make a valuable contribution if built on careful educational planning that takes into account the time and dedication of individuals, their types and styles of learning, and the true cognitive nature of a language, not just the communicative behavior that can be derived from it